Pembuatan dan Karakterisasi Ekstrak Kering Daun Salam (Syzigium polyanthum (Wight) Walp.) - Harrizul Rivai; Andi Heriadi; Humaira Fadhilah (STIFARM Padang, 2015)
The research on preparation and characterization dried extract of bay leaves (Syzigium polyanthum (Wight) Walp.) has been done. The dry extract is made by adding various ratio of lactose, which is the ratio of the extract and drying with lactose ½x heavy viscous extract (F1), lactose 1x heavy viscous extract (F2), 1½ x heavy viscous extract (F3) and lactose 2x heavy viscous extract heavy (F4). Dried extract mode with F4 has better characteristics than the other formulas. The name of the extract is Extractum Syzigium polyanthum (Wight) Walp. Siccum. The extract was in the form of dry powder, light green, odor like bay leaves with a bitter flavor. Levels of water soluble extract was 80.4343% ± 3.5790%, while levels of ethanol soluble extract 26.3056% ± 3.1693%, flavonoid levels of the dried extract was 0.4198% ± 0.2767%.